MANAJEMEN PENDIDIKAN BERASRAMA DI STAI AS-SUNNAH TANJUNG MORAWA DELI SERDANG - Bahrul Ulum; Ficki Pali Paredede; Candra Wijaya (Ristekdik : Jurnal Bimbingan dan Konseling, 2019)
This study aims to identify and analyze planning, resource management, implementation and evaluation of management of boarding education in Stai As-Sunnah Tanjung Morawa Deli Serdang.This study uses a qualitative method. The process of collecting data uses observation, interview and document study techniques. Informant chairman of Stai As-Sunnah, puket 3 and head of boarding care ... In analyzing the data the researcher used qualitative analysis with steps of data exposure, data reduction and conclusion drawing.The results of this study indicate that; 1) the planning process is carried out by deliberation followed by the chairperson of Stai As-Sunnah, puket 3 and the head of boarding and subordinates 2) the process of organizing resources with the division of tasks according to their expertise including the student executive body, preparation of daily activity schedules, monthly activity schedules and schedules annual activities 3) the process of implementing boarding education includes the implementation of a series of activities carried out by the Head of care and its staff in providing motivation, direction and guidance as well as student executive bodies based on the implementation of STAI As-Sunnah learning and activities. monthly reports and supervision of puket 3 to the dormitory when the activities are taking place.